Vertebral osteomyelitis associated with single and mixed bacterial infection in broilers. Issue 6 (1st November 2016) - Braga, Juliana Fortes Vilarinho; Silva, Camila Costa; Teixeira, Maurício de Paula Ferreira; Martins, Nelson Rodrigo da Silva; Ecco, Roselene
ABSTRACT: Vertebral osteomyelitis (VO) is a worldwide emerging disease that affects broilers. The objective of this study was to determine the frequency and aetiology of VO in broilers in a highly productive broiler region. For this, 608 broilers with locomotory problems were analysed from 18 farms. Clinical signs were recorded, necropsy was performed and samples were collected from vertebral bodies with gross changes for molecular and histopathological analysis and for bacterial isolation. From broilers with locomotory changes, 5.1% (31/608) had VO and, of these, 93.5% were 40 days old or older and 89.7% were males. The birds with VO presented varying degrees of limited mobility and this was related to the level of compression to the spinal cord. Bacterial species of the genus Enterococcus (DNA detected in 53.6%) were the aetiological agents involved in most VO cases. Enterococcus faecalis was detected most frequently (35.7%), but Enterococcus hirae was also present in some lesions (7.1%). Escherichia coli was detected in 35.7% of vertebral lesions and co-infection with E. faecalis was confirmed in 7.1% cases. Staphylococcus aureus was involved in 14.3% of the cases, being 7.1% in co-infection with Enterococcus spp. or E. hirae . Our study has indicated that, in Brazil, VO in broilers may not be caused by a single infectious agent and has a lower frequency than recently reported in other countries. This study suggests that there are geographical differences between Brazil and other countries concerning the frequency and aetiology of VO.